Nutrition Assessment in Advanced Heart Failure Patients Evaluated for Ventricular Assist Devices or Cardiac Transplantation. (9th October 2012) - Aggarwal, Ashim; Kumar, Anup; Gregory, Mary P.; Blair, Christopher; Pauwaa, Sunil; Tatooles, Antone J.; Pappas, Pat S.; Bhat, Geetha
Abstract : Background : Malnutrition has been shown to affect clinical outcomes in patients with heart failure. The aim of this study was to analyze the incidence of malnutrition and to assess its prognostic significance in patients with advanced heart failure (AHF) (being evaluated for left ventricular assist device [LVAD] or cardiac transplant) based on nutrition status as assessed by the Mini Nutritional Assessment (MNA). Methods : A retrospective analysis was conducted on 154 patients. During evaluation, a complete nutrition assessment was performed, and diagnosis of malnutrition and risk of malnutrition was done with the MNA. Its possible independent association with mortality was assessed. Results : The mean (SD) age of the patients was 59.3 (14.1) years, with 76% men. Twenty‐two percent were classified as malnourished, 68% at risk of malnutrition, and 10% well nourished. The mortality in the 3 groups was 26.5%, 42.0%, and 6.7%, respectively ( P = .02). In the multivariate logistic regression analysis, the undernutrition state (malnourished + at risk) was an independent predictor of mortality (odds ratio, 7.9; confidence interval, 1.01–62.30; P = .04). Conclusions : The state of undernutrition is an independent predictor of mortality in patients with AHF. Early recognition of undernutrition through use of the MNA may affect the long‐term prognosis of these patients by enabling early intervention.